PENGEMBANGAN MEDIA PEMBELAJARAN ANIMASI MENGGUNAKAN POWTOON UNTUK MATERI MENULSI KARYA ILMIAH SISWA KELAS XI SMA - Vernanda, Yudha; Charlina; Septyanti, Elvrin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to develop Powtoon-based animated learning media for scientific writing materials for eleventh-grade senior high school students and to examine its validity, practicality, and effectiveness. This research employed the Research and Development (R&D) method using the Four-D (4D) model, consisting of the define, design, develop, and disseminate stages. The participants were 40 students of class XI IPS 3 at SMAN 10 Pekanbaru. Data were collected through interviews, questionnaires, documentation, and pre-test and post-test assessments. The results indicated that the developed media was highly valid, with language expert validation of 84.6% and material expert validation of 91%. Practicality testing showed positive responses from students (86.7%) and teacher practitioners (88%), both categorized as highly practical. The effectiveness test demonstrated an improvement in students’ average scores from 79.00 to 85.92. The Wilcoxon Signed Rank Test showed a significant difference between pre-test and post-test results (Asymp. Sig. = 0.001 < 0.05), while the N-Gain score of 0.31 indicated a moderate improvement. These findings suggest that the Powtoon-based animated learning media is valid, practical, and sufficiently effective for teaching scientific writing.